2013
DOI: 10.1103/physrevb.87.224303
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigation of the low-temperature dynamics of solid4He doped with3He impurities

Abstract: The lattice dynamics of solid 4 He has been explored using pulsed NMR methods to study the motion of 3 He impurities in the temperature range where experiments have revealed anomalies attributed to superflow or unexpected viscoelastic properties of the solid 4 He lattice. We report the results of measurements of the nuclear spin-lattice and spin-spin relaxation times that measure the fluctuation spectrum at high and low frequencies, respectively, of the 3 He motion that results from quantum tunneling in the 4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Several nuclear magnetic resonance studies have shown that at low temperatures 3 He atoms in solid 4 He behave as quantum quasi-particles that can move through the lattice at velocities as high as ∼ 1 mm/s (Allen, Richards, and Schratter, 1982;Kim et al, 2013), that is, significantly higher than 45 µm/s. It has been argued then that near the dislocation the mobility of isotopic impurities could be reduced considerably by the existing local strain (Balibar et al, 2016); however, there is not quantitative evidence showing that such a huge variation of about three orders of magnitude in the mobility of 3 He impurities could be actually possible.…”
Section: B Dislocationsmentioning
confidence: 99%
“…Several nuclear magnetic resonance studies have shown that at low temperatures 3 He atoms in solid 4 He behave as quantum quasi-particles that can move through the lattice at velocities as high as ∼ 1 mm/s (Allen, Richards, and Schratter, 1982;Kim et al, 2013), that is, significantly higher than 45 µm/s. It has been argued then that near the dislocation the mobility of isotopic impurities could be reduced considerably by the existing local strain (Balibar et al, 2016); however, there is not quantitative evidence showing that such a huge variation of about three orders of magnitude in the mobility of 3 He impurities could be actually possible.…”
Section: B Dislocationsmentioning
confidence: 99%
“…In 4 He crystals, large quantum fluctuations have at least two important consequences. First, 3 He atoms move freely at velocities of order 1 cm/s through the lattice [5,6]. They can also bind to dislocations [7,8], in which case there is a thermodynamic equilibrium between the bound 3 He atoms in the potential well of dislocation cores and a gas of free 3 He quasiparticles in the bulk crystal.…”
mentioning
confidence: 99%